SWITCHING FROM ORAL HYPOGLYCEMIC DRUGS TO INSULIN: HURDLES AND REMEDIES - Ahmed, Ibrar (Journal of Postgraduate Medical Institute, 2020)
To start with I want to quote Dr. Frederik Banting "Insulin does not belong to me; it belongs to the world"1. Diabetes mellitus is one of the endocrine endemics arising in our country in recent years. According to the recent IDF Atlas 2019, Pakistan is at No. 4 in the prevalence of Diabetes2. People and physicians were thinking that diabetes is a bomb which is about to explode but the recent published data of diabetes prevalence survey of Pakistan (DPS-PAK)3 showed that it had already exploded. Therefore, we should emphasize on relevant measures that should be taken in already diagnosed diabetics. They should be treated with care and prompt action needs to be taken at proper time to prevent or delay complications. Oral hypoglycemic agents are frequently not sufficient to control glycemic status and insulin therapy is required. One of the foremost action is to start insulin at proper time; however, as health care professionals we come across a lot of hurdles in initiation of insulin. These are many fold and vary from opinions of relatives, parents, physicians, quacks, medical store owners, lab technicians to social issues or economic burden and patient's beliefs against starting insulin4-6.